Radiation Safety Culture: The Way Forward in Practicing Interventional Radiology - Roshan S. Livingstone; Anna Varghese (Journal of Clinical Interventional Radiology ISVIR)
Radiation dose from catheter-based interventional procedures performed in catheterization laboratories are of concern as an increase of radiation dose beyond threshold limits will be detrimental to the patient. It is important that radiation personnel understand the biological effects of radiation since patient and staff exposure may be significantly high when not adhered to radiation safety standards. Use of protective accessories, such as lead aprons and goggles, has been practiced worldwide for individual protection. Dose audit during interventional procedures is important for the benefit of the patient. Several factors including angiographic equipment, preset protocols, and tube angulations that influence radiation dose to patient and operators and hence modification on radiation safety work practices in the catheterization lab is warranted. Implementing periodic radiation safety training for occupational workers would be beneficial to practice a radiation safety culture.